2014
DOI: 10.1210/jc.2013-3539
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Promoter Region of the Selenoprotein S Gene (SEPS1) Contributes to Hashimoto's Thyroiditis Susceptibility

Abstract: Our findings support the existence of a link between SEPS1 promoter genetic variation and HT risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 17 publications
1
53
1
2
Order By: Relevance
“…The major allele C and genotype CC in SELENOS rs7178239 showed different trend in GD and HT patients when compared to the control. While the major allele C and CC genotype in rs28665122 of SELENOS increased in both GD and HT patients than the control, different to the result for another study, in which these allele and genotype decreased significantly in their HT patients [14]. Our association analysis showed negative and the distribution difference showed nonsignificant.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The major allele C and genotype CC in SELENOS rs7178239 showed different trend in GD and HT patients when compared to the control. While the major allele C and CC genotype in rs28665122 of SELENOS increased in both GD and HT patients than the control, different to the result for another study, in which these allele and genotype decreased significantly in their HT patients [14]. Our association analysis showed negative and the distribution difference showed nonsignificant.…”
Section: Resultscontrasting
confidence: 99%
“…Our results were conflicted to the result from the Portuguese population study. In that study, the higher allele A in SELENOS rs28665122 had been found to be associated with the HT risk [14]. Different selenium nutrition state in different populations may contribute to conflicting results, the contribution of genetic variants in AITD mechanism may be another reason.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are still urgent research questions concerning the importance of baseline Se status for successful supplementation and about potential genetic/sex-specific differences in Se metabolism [31] . Ongoing studies will clarify how endocrinologists can appropriately determine Se treatment for thyroid disease management [16,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the family of selenoproteins has been described in correlation with these two maladies since selenium has one of the highest concentrations in thyroid and the enzymes using it as co-factor are involved in oxidative status, thyroid hormone synthesis, immune modulation and mutagenesis [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%